A Cross-Linked Poly(Ethylene Oxide)-Based Electrolyte for All-Solid-State Lithium Metal Batteries With Long Cycling Stability - Xin, Chengzhou; Wen, Kaihua; Guan, Shundong; Xue, Chuanjiao; Wu, Xinbin; Li, Liangliang; Nan, Ce-Wen (Frontiers in Materials, 2022)
A cross-linked poly(ethylene oxide) (PEO)-based electrolyte with polyaryl polymethylene isocyanate (PAPI) as the cross-linking agent is synthesized by a facile one-pot reaction. The PEO chains are cross-linked by PAPI through the reaction between hydroxyl groups (−OH) and isocyanate groups (−N=C=O). The effects of PAPI on the electrochemical performance of the PEO-based electrolyte and the stability of the electrolyte/electrode interface are investigated. The PEO–PAPI electrolyte has an ionic conductivity of 9.3 × 10–5−1.3 × 10–4 S cm−1 at 60°C. The cross-linked PEO–PAPI electrolyte exhibits enhanced mechanical properties compared to pristine PEO and shows good compatibility with a lithium (Li) metal anode. An all-solid-state Li metal battery (ASSLMB) with the optimized PEO–PAPI electrolyte and a LiFePO4 cathode (1.62 mg cm−2 in mass loading) shows a discharge capacity of 112.8 mAh g−1 after 700 cycles with a current density of 88 μA cm−2 at 60°C. Even with a high mass loading of 8.4 mg cm−2, the ASSLMB with the cross-linked PEO-based electrolyte shows a good cycle performance. The experimental data show that the cross-linked PEO–PAPI electrolyte is a promising candidate for solid electrolytes used in ASSLMBs.